2022
DOI: 10.3390/ma15030910
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Treatment on End Notched Flexure Bonded Joints in Carbon Fiber Reinforced Polymer: Experimental and Numerical Results

Abstract: Surface pretreatment for bonding is one of the most important steps for the manufacturing of a reliable bonded joint. In this paper, the effectiveness of an innovative pretreatment by CO2 pulsed laser for bonding Carbon Fiber Reinforced Polymer (CFRP) was investigated. End Notched Flexure (ENF) specimens were made with different densities of laser treatment, and the respective fracture toughness was obtained through the Compliance-Based Beam Method (CBBM). Furthermore, a cohesive model for simulating debonding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In previous works of the authors, densities of treatment until 35% were investigated and correlated to the mechanical performance of end-notched flexure specimens. 8 The results showed that a density of treatment of 20% is connected to higher mechanical resistance. For this reason, a density of treatment of 20% has been adopted in this work.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous works of the authors, densities of treatment until 35% were investigated and correlated to the mechanical performance of end-notched flexure specimens. 8 The results showed that a density of treatment of 20% is connected to higher mechanical resistance. For this reason, a density of treatment of 20% has been adopted in this work.…”
Section: Methodsmentioning
confidence: 97%
“…5,6 Plasma and laser pre-treatments represent a valid alternative to traditional pre-treatments as they allow to of creation a rough surface in a repeatable and accurate way without using contact tools, which could contaminate the surface to be bonded. [7][8][9] Laser texturing for bonding CFRP laminates has been investigated by Palmieri et al 10 : they studied the relation between contact angle and ablation patterns, observing that the contact angle was stable within some time from the moment the pre-treatment was made. Energetic methods such as plasma and laser treatment make the surface of the CFRP chemically more reactive, as these methods involve breaking the superficial molecular bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In this application, it is important to save the lubricant and decrease the coefficient of friction. Other possible applications are the increase in heat dissipation [19], reduction in corrosion of stainless steels [20], or enhancement of the adhesion with other substrate types [21].…”
Section: Introductionmentioning
confidence: 99%
“…The use of adhesives in bonded joints provides some key advantages over traditional mechanical fasteners, such as reduced stress concentration, improved damping properties, higher fatigue strength and lighter structures. [1][2][3] The techniques to predict the static strength of bonded joints is well widespread and have great importance since it allows engineers to design robust models. However, in many practical applications the bonded structures remain loaded for long times, for example, in (1) aircrafts: stringers in both fuselages and wings, ailerons and spoilers, 4 or (2) automobiles: front hood, roof to body side, door hinge reinforcement panels.…”
Section: Introductionmentioning
confidence: 99%